Acquiring and development of teachers' e-competences in the system of qualification improvement - O. P. Suk (Academy of Cognitive and Natural Sciences, 2014)
Research goals: expansion of the IT component of system of teachers' training. Research objectives: to provide guidance on the methodology of certain types of studies and scenario for building of seminar for teachers depending on the capabilities and desires of students and choice of e-Competences. Object of research: the system of qualification improvement. Subject of research: acquiring and development of teachers' e‑competences in the system of qualification improvement. Research methods used: analysis of international standards, publications and educational process. Results of the research. In the paper it's described the experience and practical results that was obtained in the training of teachers from Ukrainian HEI in the seminar of qualification improvement "Management of Distance Education", which for many years is conducted at the Centre of Distance Education of National Technical University «Kharkiv Polytechnic Institute». The main objective of the seminar is to acquire its audience a set of e-competences that will enable them to start or speed up the implementation of the methodology and tools of e-learning in their departments. The seminar is based on a blended learning. The main conclusions. It's shown that the chosen methodology, together with the use of numerous practical results of NTU "KPI" System of Distance Education, is optimal for achieving this goal.